The Invention of Fanaticism - Cavanaugh, William T. (Modern theology, 2011)
This article examines the Western construction of "religion" as passionate and non-rational. First, it summarizes the history of the category "religion" and the creation of the myth of religious violence. It then examines the construction of one of the stock characters of modernity, the religious fanatic, and shows how fanaticism migrated from an accusation against heretics to an accusation of intolerance, and from an indictment of false prophecy and belief to an indictment of an irrational and violent passion. The article then shows how the construction of "religious fanaticism" can promote secularist rationales for violence.